United States : Publication of Financial Sector Assessment Program Documentation; Detailed Assessment of Observance of the National Securities Clearing Corporation's Observance of the CPSS-IOSCO Recommendations for Central Counterparties. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
This paper discusses key findings of the Detailed Assessment of Observance of the National Securities Clearing Corporation's (NSCC) Observance of the Committee on Payment and Settlement Systems/International Organization of Securities Commissions (CPSS-IOSCO) Recommendations for Central Counterparties (CCP) for the United States. The assessment recommends that a CCP should have a well-founded, clear, and transparent legal basis in the relevant jurisdictions. A CCP should require participants to have sufficient financial resources and robust operational capacity to meet obligations arising from participation in the CCP.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet